ʺInformation and communication technologies for teaching physics of future specialists in computer engineering under the remote learningʺ. - Synelnyk, I.; Synelnyk , O. (Problems of Engineer-Pedagogical Education, 2024)
Transformational changes in society, social and political realities caused the education system of Ukraine to function mainly online. The lack of a general psychological and pedagogical theory of remote learning makes it urgent to search for ways to improve the quality of learning through the creation and harness of information and communication technologies that provide a solution to the problems arising in online studying. The article presents a study of the process of teaching physics to students of IT specialties in remote learning and reasoning of the methods of using computer tools and information and communication technologies in the studying process. The differences between the remote form of studying and distance learning have been explained, the peculiarities of the students have been clarified, the specifics of physics as a fundamental educational subject and a component of the professional training of future specialists in the field of computer engineering in the context of remote learning have been revealed. Based on the content of the discipline and the types of learning and teaching activities, the selection criteria, expediency of development and methods of usage of information and communication technologies for solving the certain didactic tasks are substantiated. There were proposed methods of usage dynamic computer presentations for the delivering theoretical material and providing analytical symbolic activity; an interactive board for the organization of students' practice work and the physics problems solving; software for computer simulation of physical processes to acquire skills of doing computer experiments; electronic templates with an automated checkup function for representation the results of students’ independent work; computer testing as the basis for monitoring of students learning activity.